Lactic acid bacteria : microbiological and functional aspects - Salminen, Seppo (Boca Raton : CRC Press, Taylor and Francis, 2012)
"Updated with the substantial progress made in lactic acid and bacteria research since the third edition, this fourth volume discusses improved insights in genetics and new molecular biological techniques. Thoroughly reorganized, this book incorporates the recent changes in new molecular techniques and the mechanistic understanding of probiotic functionality. The book remains firmly grounded in the basics of lactic acid bacteria; their genetics and taxonomy, their application in food and feed preparation, their health properties, and the legal issues associated with their use"--Provided by publisher.
"A CRC title."
Includes bibliographical references and index.
Keywords: Lactobacillus -- genetics; Food Microbiology; Lactobacillales -- genetics; Molecular Diagnostic Techniques